A paradigm change to inform fibromyalgia research priorities by engaging patients and health care professionals. Issue 1 (1st January 2017) - Fitzcharles, Mary-Ann; Brachaniec, Mary; Cooper, Lynn; Dubin, Ruth; Flynn, Trudy; Gerhold, Kerstin; Häuser, Winfried; Cowan, Katherine; Laupacis, Andreas; Marleau, Renee; Milot, Marc; Szajcz-Keller, Nicole; et al.
ABSTRACT: Background : Research objectives should be focused toward advancing knowledge that has meaningful impact on health. However, research agendas are mostly driven by the health care community, with limited input from patients. Aims : In this study, prioirities of uncertainties for the management of fibromyalgia (FM) that could propel future research were identified by a defined process using the James Lind Alliance Priority Setting Partnership (JLA-PSP) methodology. Methods : As a first step, a survey was distributed across Canada that engaged patients, caregivers, and health care professionals to provide narrative input to eight open-ended questions regarding FM care. Responses were thematically condensed and synthesized into an initial list of 43 uncertainties used to guide a comprehensive literature search. Questions already effectively addressed in the literature were excluded, leaving 25 uncertainties that were ranked during a one-day consensus workshop. Results : Three broad themes emerged: the value of personalized targeted treatment and subgrouping of patients; the efficacy of various self-management strategies and educational initiatives; and identification of the ideal health care setting to provide FM care. Opioids and cannabinoids were the only specific pharmacologic interventions ranked as needing further research. Conclusions : The prioritized questions highlight the importance of recognizing the heterogeneity of FM symptoms, the need for a personalized treatment approach, and a better understanding of the value of self-management strategies. This is the first study that uses an established and transparent methodology to engage all FM stakeholders to help inform researchers and funding bodies of clinically relevant research priorities.